Pengembangan Media Video Tutorial pada Pembuatan Desain Busana Anak Secara Digital Berbasis Sketchbook di Kelas XI SMK Negeri 1 Jabon - Risma Fajiyah; Deny Arifiana; Mita Yuniati; Mein Kharnolis (Departement of Mathematics Education, 2024)
This research is a development research with the ADDIE model which aims to (1) describe the feasibility of video tutorial media for making digital children's fashion designs based on sketchbooks and (2) describe student learning outcomes in the psychomotor domain or skills after applying video tutorial media. The subjects of this study were students of class XI Tata Busana 2 at SMK Negeri 1 Jabon, totalling 36 students. Data collection was carried out through feasibility validation questionnaires and student learning outcomes, with quantitative descriptive data analysis techniques. The results of this study indicate (1) the results of the feasibility of video tutorial media developed are very feasible to apply, by obtaining a feasibility percentage by material experts of 92.5% and a feasibility percentage by media experts obtaining 92.67%, (2) student learning outcomes in the psychomotor domain or skills after applying the developed video tutorial media reached an average value of 88.2 with a very good category and achieved learning completeness with a percentage of 94% complete.